EFFICACY AND SAFETY OF USING MOMETASONE FUROATE IN CHILDREN WITH ATOPIC DERMATITIS - A.Yu. Tomilova; R.M. Torshkhoeva; A.K. Gevorkyan; N.I. Voznesenskaya (Педиатрическая фармакология)
The article describes the therapy for atopic dermatitis with topical glucocorticosteroids. Parameters of the «ideal» topical cortico steroid are provided: strong anti-inflammatory effect, low systemic bioavailability, quick action onset, minimal side effects, multiplicity of pharmaceutical forms. It describes results of a number of clinical trials for efficacy and safety of using mometasone furoate in children, a pharmaceutical product close enough to the «ideal» characteristics of a topical corticosteroid.Key words: atopic dermatitis, topical glucocorticosteroids, mometasone furoate, children, safety.